2022
DOI: 10.52017/001c.37901
|View full text |Cite
|
Sign up to set email alerts
|

The Pros and Cons of Consolidating Rehabilitation Counseling Associations: A Qualitative Analysis of Views From the Field

Abstract: The potential for unification of rehabilitation counseling professional associations has been a conceptual debate for the past several decades. In a previous article of this special issue, Phillips et al. (2022) provided quantitative data to capture the opinions of professionals on the issue of consolidation. The present study builds on those findings by providing a qualitative analysis of the rationale provided for each response from not only professional association members, but the broader rehabilitation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Phillips, Walker et al conclude the results by exploring factors that may influence perceptions of whether to consolidate. In the next article of the special issue, Nerlich et al (2022) provide a qualitative analysis of the rationales provided by rehabilitation counseling professionals for their choice in favor of, opposed to, or unsure about consolidation. They found that a significant majority of those reporting they were unsure about consolidation lacked familiarity with the associations or with the debate about consolidating them.…”
Section: The Current Special Issuementioning
confidence: 99%
“…Phillips, Walker et al conclude the results by exploring factors that may influence perceptions of whether to consolidate. In the next article of the special issue, Nerlich et al (2022) provide a qualitative analysis of the rationales provided by rehabilitation counseling professionals for their choice in favor of, opposed to, or unsure about consolidation. They found that a significant majority of those reporting they were unsure about consolidation lacked familiarity with the associations or with the debate about consolidating them.…”
Section: The Current Special Issuementioning
confidence: 99%
“…Phillips et al (2022) also showed that increased familiarity with these associations and with the issues surrounding consolidation correlated with an increased desire to consolidate. Delving further into the qualitative data, suggested that professionals perceive many potential benefits resulting from a consolidated rehabilita-tion counseling professional association (Nerlich, Levine, et al, 2022). Themes among the 1,033 who provided a response in favor of consolidation included increased unity, a stronger external voice, cost savings, streamlined processes, reduced confusion, and the belief that it would generate greater membership.…”
mentioning
confidence: 99%